2018
DOI: 10.1002/admi.201800022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the NO Anneal on the Microscopic Structure and Chemical Composition of the Si‐Face 4H‐SiC/SiO2 Interface

Abstract: Understanding the microscopic structure of the SiC/SiO2 interface is crucial for the improvement of SiC based metal‐oxide‐semiconductor field‐effect transistors (MOSFETs). It is well established that interface states degrade the performance and reliability of SiC MOSFETs and that passivation can be achieved by anneals in NO‐containing atmospheres. However, the structural changes associated with the NO anneal and the improvement of the channel electron mobility are still not fully understood. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…12,48 In the context of the interface described for this generation of devices, the highly-stepped nature of the interface can be understood to give rise to a high number of sites where P bC and dual-P bC could be accommodated. Quantitatively, it is impossible to gauge the concentration of these sites; however, qualitatively from the previous TEM studies, 25,27,32,47 the interface can be understood to be continuously stepped with a greater area than the observed terraces. Finally, it is interesting to note that there is a small asymmetry in the observed spectra which is consistent with minority population of an isotropic defect that is offset by approximately 2-3 G. This matches the g-value and the angular behavior of the V Si at approximately 5%-10% of the intensity of the center line (P bC & dual-P bC ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,48 In the context of the interface described for this generation of devices, the highly-stepped nature of the interface can be understood to give rise to a high number of sites where P bC and dual-P bC could be accommodated. Quantitatively, it is impossible to gauge the concentration of these sites; however, qualitatively from the previous TEM studies, 25,27,32,47 the interface can be understood to be continuously stepped with a greater area than the observed terraces. Finally, it is interesting to note that there is a small asymmetry in the observed spectra which is consistent with minority population of an isotropic defect that is offset by approximately 2-3 G. This matches the g-value and the angular behavior of the V Si at approximately 5%-10% of the intensity of the center line (P bC & dual-P bC ).…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by Raman, TEM, and electron energy loss spectroscopy (EELS) studies, showing no significant C-concentration in the interface and near interface region. 2,[24][25][26][27][28][29][30][31][32] While these methods cannot completely rule out the presences of a C-excess ([C] < 1%) at the interface, it is clear that recently characterized devices do not show the same C-rich layer that was present in the earlier devices. In itself this would be insufficient to rule out the presence of C-dimer like defects; fortunately, these defects have been extensively studied both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NO or N 2 O annealing, which is a typical method for POA, causes negative charge states at the SiO 2 /SiC interface. [24][25][26][27][28] MFZ-JTE is an alternative edge termination structure, which is theoretically less affected by Q surf and changes in pattern size. 29,30) However, a conventional MFZ-JTE has significantly narrow spaces in the early part of the edge termination structures.…”
Section: Introductionmentioning
confidence: 99%
“…The types of defects postulated around the SiC/SiO 2 interface include dangling bonds in SiC, defects in the SiO 2 , silicon oxycarbides (SiO x C y ) and silicon oxynitrides (SiO x N y ). [6][7][8][9][10][11] In order to improve performance and reliability of SiC-based devices, SiC/SiO 2 stacks are subjected to high temperature thermal treatments in nitrogen-containing atmospheres. NO is the most widely explored annealing atmosphere and consistently shows great improvement of device performance.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this limitation is that the characterisation of heterostructures, including buried layers and interfaces within them, presents a challenge for many established characterisation techniques and necessitates the use of very advanced techniques. [10,[15][16][17][18] An established materials characterisation technique that has been applied extensively to the investigation of SiC/SiO 2 structures after nitridation, contributing to our current understanding of the system, is X-ray photoelectron spectroscopy (XPS). [7,13,[19][20][21] We recently showed that soft X-ray photoelectron spectroscopy (SXPS) is a powerful technique to probe the chemical state of the SiC/SiO 2 system.…”
Section: Introductionmentioning
confidence: 99%